2019
DOI: 10.1021/acsbiomaterials.9b01528
|View full text |Cite
|
Sign up to set email alerts
|

Sic Parvis Magna: Manganese-Substituted Tricalcium Phosphate and Its Biophysical Properties

Abstract: Succeeding in the substitution of pharmaceutical compounds with ions deliverable with the use of resorbable biomaterials could have far-reaching benefits for medicine and economy. Calcium phosphates are known as excellent accommodators of foreign ions. Manganese, the fifth most abundant metal on Earth was studied here as an ionic dopant in β-tricalcium phosphate (β-TCP) ceramics. β-TCP containing different amounts of Mn2+ ions per Mn x Ca3–x (PO4)2 formula (x = 0, 0.001, 0.01, and 0.1) was investigated for a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 58 publications
3
48
0
Order By: Relevance
“…The growth of cell mass on the surface of the Mn-TCP coating occurs faster compared to the TCP coating’s surface, which is likely due to the influence of the manganese. This observation is confirmed by our previous studies regarding the Mn-TCP powders with different concentrations of Mn [ 12 ]. It was found that Mn ions have a positive effect on adipose-derived mesenchymal stem cells’ viability and proliferation, demonstrating no inhibitory or adverse effects, and on cells differentiation into osteogenic, adipogenic, and chondrogenic lineages.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The growth of cell mass on the surface of the Mn-TCP coating occurs faster compared to the TCP coating’s surface, which is likely due to the influence of the manganese. This observation is confirmed by our previous studies regarding the Mn-TCP powders with different concentrations of Mn [ 12 ]. It was found that Mn ions have a positive effect on adipose-derived mesenchymal stem cells’ viability and proliferation, demonstrating no inhibitory or adverse effects, and on cells differentiation into osteogenic, adipogenic, and chondrogenic lineages.…”
Section: Resultssupporting
confidence: 90%
“…Further increase of manganese amount is followed by the EPR spectrum narrowing, due to the exchange interaction. From the comparison of the obtained EPR pattern ( Figure 3 ) with the results presented in [ 12 ], one can give the estimation of the Mn 2+ amount in the investigated powder as higher than 2 wt%, which is in good agreement with the results obtained by the EDX analysis.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations